Abordagem do fenômeno da supercondutividade na educação básica - Silva, Daniel Gomes da (Brasil, 2022)
The present dissertation consists of the creation and proposal of using an educational product in the form of a comic book - HQ to help Physics teachers in the introduction of the concepts of superconductivity with high school students. The aforementioned HQ is our authorship consisting of an e-book entitled “Learning about superconductivity with Nando”. It portrays the learning of Fernando, a high school student, regarding the phenomenon of superconductivity and the support of his Physics teachers in helping him along this path. The plot was all built from the Pixton online software. We emphasize that this educational product can be used as an auxiliary means for classes that deal with this subject, in addition to being an alternative way to deal with the subject given the high costs of an experimental approach. The educational product was submitted to a research whose focus can be characterized by qualitative, exploratory and descriptive. The possibilities of learning the theme from the interaction with the proposed e-book were examined. It should be noted that this educational product was applied in times of the COVID-19 pandemic remotely with synchronous and asynchronous activities. The data results were analyzed and discussed in this dissertation. The conclusion is that the learning of the phenomenon of superconductivity can be mediated by the use of comic books.